Clinical Spectrum of Pediatric Traumatic Brain Injury—A Prospective Observational Study - Shiji Chalipat; Sandeep Kumar; Sudhir Malwade; Vishwanath Kulkarni; Jeevana Bollineni (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: Traumatic brain injury (TBI) is a significant global health concern and a leading cause of mortality and morbidity in children. Understanding injury patterns and outcome variables can aid in better management and improved neurodevelopmental outcomes. Methods: An observational prospective study was done over two years and the study population included children aged three months–12 years within 72 hours of head injury. Clinical profile, neuroimaging patterns, management, and outcome on discharge were analyzed. Results: Out of 95 children, the mean age was 4.66 ± 3.61 years and M/F 1.76:1. Mild TBI was seen in 70.5%, moderate TBI in 19%, and severe TBI in 10.5% of children. Fall from height was the most common mode of injury and abnormal neuroimaging was noted in 69.4% of children. Fracture skull was the most common neuroimaging abnormality found. Conservative management was the main mode of treatment, 30 children (31.6%) required intensive care, and surgical intervention was required in eight children (8.4%). The mean duration of hospital stay was 5.29 ± 6.6 days. Overall mortality rate was 2%, good outcome was noted in 88 (92.6%) and poor outcome in seven children (7.3%). The factors associated with poor outcomes were severe TBI, signs of raised ICP, abnormal neurological examination, and mode of injury by RTA. Conclusions: TBI is more commonly seen in school-aged children, accidental falls being the most common mode of injury. The majority of children had mild TBI and the overall outcome was really good. The most effective predictor of poor outcome was GCS-based TBI severity grading.